Management Control Systems and HEI Performance: The Mediation of Knowledge Sharing - Suryadi, Nanda; Yusnelly, Arie; Farwitawati, Reni; Rimet, Rimet (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of enabling control systems and coercive control systems on higher education institutions (HEI) performance with knowledge sharing as a mediating variable. The research was conducted on 384 respondents from the academic community in various HEI. The analysis method used was Partial Least Square (PLS) with the help of SmartPLS 4 software. The results showed that both enabling control systems and coercive control systems had a positive and significant effect on HEI performance. In addition, both types of control systems were also found to have a positive effect on knowledge sharing. Other findings show that knowledge sharing has a significant positive effect on HEI performance and is able to mediate the relationship between control systems and institutional performance. Theoretically, this study reinforces the Resource-Based View (RBV) concept by emphasizing the important role of knowledge-based capabilities as strategic resources. Practically, the results of this study have implications for HEI managers to balance the application of control systems that are supportive and demand compliance, as well as encourage a culture of knowledge sharing to improve the quality and competitiveness of the institution